Answer:
Thhe simplified form of the expression is 9
Indices are expressed as power or exponent which is raised to a number or a variable.
According to the law of indices
\begin{gathered}a^n \times a^m = a^{n+m}\\a^n \div a^m = a^{n-m}\end{gathered}
a
n
×a
m
=a
n+m
a
n
÷a
m
=a
n−m
Given the expression
3^{-6} \times (\dfrac{3^4}{3^0} )^23
−6
×(
3
0
3
4
)
2
This can also be expressed as:
\begin{gathered}=\dfrac{1}{3^6} \times (\frac{3^4}{1})^2 \ (3^0 =1)\\= \dfrac{1}{3^6} \times 3^8\\=\dfrac{3^8}{3^6}\\=3^{8-6}\\=3^2\\=9\\\end{gathered}
=
3
6
1
×(
1
3
4
)
2
(3
0
=1)
=
3
6
1
×3
8
=
3
6
3
8
=3
8−6
=3
2
=9
This shows that the simplified form of the expression is 9